G117(P) Impact of an early warning system for nursing observations in at-risk neonates in the post natal wards. (27th April 2015) - Pillay, T; Doodson, M; Nash, M; Moore, R
Abstract : Aim: In line with national recommendations for similar systems in other disciplines, the SSBCNN implemented an Early Warning System (EWS) for nursing observations in the at-risk neonate on the post natal ward. The impact on nursing workload, utility and efficiency of this EWS was audited, as part of an initiative to understand trigger events for intervention in at-risk babies. Method: Case notes of 300 neonates following implementation of EWS, and 240 predating its implementation were reviewed. In the latter a retrospective EWS chart was completed using data extracted from notes. Early warning triggers were observations falling outside the acceptable colour coded range. Observations were analysed in at-risk neonates with meconium stained liquor, maternal history of prolonged rupture of membranes, maternal group B Streptococcus infection and small for gestational age. Feedback from 56 nurses in the network was obtained using a structured questionnaire. Results: A nursing observation that was intended to trigger an intervention was reached in 261(48.3%) at-risk babies. Intervention was recorded in 25%; in the remainder, no action was taken, or none documented. Low temperature (<36.5°C) was the commonest trigger. In subgroup analyses, 41.8% of hypothermia was recorded within the first 2 h of birth. 1.7% babies were admitted to the neonatal unit in response to trigger observations. Fewer trigger observations were noted in the post-implementation group (144/240 vs 117/300; p= <0.01). This was specifically significant for hypothermia (125/240 vs 88/300; p= <0.001). The EWS did not increase the number of observations per category of stable at-risk neonates. The duration of hospital stay was 10–14 h shorter post-implementation of EWS in those babies delivered vaginally. Nursing feedback was positive in all; 82% had used the chart in >20 with 30% having used it in over 50 babies each, prior to responding. Conclusion: The implementation of EWS was associated with a reduction in trigger observations, implying improved neonatal clinical condition, specifically temperature control. This improvement infers greater attention to detail accompanying systematic recording of observations; however, a direct association between the two cannot be proved. The EWS did not increased nursing workload, and contributed to increased efficiency, measured through shorter hospital stays for those born vaginally.